Tribological and Vibration Studies of Textured Spur Gear Pairs under Fully Flooded and Starved Lubrication Conditions. Issue 6 (1st November 2020) - Gupta, Niharika; Tandon, N.; Pandey, R. K.; Vidyasagar, K. E. Ch.; Kalyanasundaram, Dinesh
Abstract: The tribological and vibrational behaviors of conventional and textured spur gear pairs were experimentally explored under fully flooded and starved lubrication conditions at different operating parameters. Three different gear tooth profile textures were created by creating vertically oriented ellipsoid, horizontally oriented ellipsoid, and hemispherical dimples in zigzag patterns using a nanosecond pulsed fiber laser. Tribological parameters (contact resistance, temperature rise, and surface topography) and vibration (in time and frequency domains) were obtained, compared, and analyzed. The results revealed a reduction in vibration amplitudes, increase in contact resistance, decrease in temperature rise, and less damage of mating surfaces in the presence of textures. Moreover, the texture with vertically oriented ellipsoidal dimples yielded the best results.